EU BORDER SECURITY – THE DRIVERS AND BARRIERS OF BORDER GUARDING AUTHORITIES MOTIVATION IN TECHNOLOGICAL INNOVATION. CASE OF LATVIA - Kublickis, Raimonds (Border Security and Management, 2020)
With the dynamic development of modern society, ensuring the security and control of the state border is the simultaneous goals of both internal and external security of the country. Consequently, it is vitally important to identify and develop tools and ways to address emerging challenges. In the current climate, private and public organizations are required to be up-to date with technological advancements in order to provide competitive, relative and effective solutions and services for inhabitants in all areas. Technological innovation is an important and even compulsory element of the modern organization, which stimulates continuous development and potential growth. There are many innovative ideas within other industries and universities where joint funds could be sort to allow the delivery of innovative solutions that would benefit such law enforcement agencies as border guarding authorities.  A significant problem is that there appears to be a lack of interest from the respective law enforcement organizations in participating in consortiums, which is necessary for submission of any proposal. Jon Freemans` Analytical framework for understanding of innovation process used to under pin the main concepts of the research proposed in this thesis. This research involved a series of interviews and questionnaires designed to analyse the perceptions of the drivers and barriers of the State Border Guard of Latvia. From detailed results analysis, a list of general recommendation been established for Border Guarding Authorities in order to improve its motivation for participation in the projects related development of the technological innovation in the field of border security by conducting internal measures and improving network/connection building outside of the organization.